Age of acquisition (AoA) effect in monolingual Russian and bilingual Russian (L1)-English (L2) speakers in a free recall task. Issue 2 (3rd July 2017) - Volkovyskaya, Evgenia; Raman, Ilhan; Baluch, Bahman
ABSTRACT: AoA is a unique psycholinguistic variable because of its link to the semantic architecture of the mental lexicon. The role of AoA on free recall has been examined in English and recently in Turkish with contradictory outcomes. The present study extends Raman et al.'s (under revision, Differential effects of age of acquisition and frequency on memory: Evidence from free recall of pictures and words in Turkish) study to monolingual Russian and bilingual Russian (L1)-English (L2) speakers in order to understand the extent to which AoA affects free recall. Participants were allocated to either picture or word condition and subsequently to either pure list or mixed list condition. Both monolingual Russian (N = 42) and bilingual (N = 40) Russian (L1)-English (L2) data show a robust main effect for AoA in free recall irrespective of list type for words and for pictures and no significant interactions. Overall, early acquired words and pictures had an advantage over late acquired items. These findings are contrary to what has been reported in the literature for monolingual English speakers but in line with findings for Turkish and will be discussed within the monolingual and bilingual theoretical frameworks.